A systematic review of emotion regulation in children with Autism Spectrum Disorder - Cibralic, Sara; Kohlhoff, Jane; Wallace, Nancy; McMahon, Catherine; Eapen, Valsamma (Research in autism spectrum disorders, 2019)
•Young children with ASD have poorer ER abilities than typically developing children.•Young children with ASD rely more on others to regulate their emotions.•ASD symptom severity and low executive functioning are associated with poorer ER abilities.•Caregivers of children with- and without- ASD are comparable on sensitivity, responsiveness and limit setting. Autism Spectrum Disorder (ASD) has significant negative impacts on a child’s development as well as their family’s social, emotional, and economic wellbeing. In an effort to better understand the aeitology of ASD and therefore provide interventions for children on the autism spectrum, various factors have been taken into consideration, one of which is emotion regulation (ER) ability. This paper sought to synthesize the current research on ER in children, specifically young children (aged 12–72 months), with ASD to better understand the association between ASD and ER in young children. Research databases and reference lists of relevant papers were searched systematically for articles on ASD and ER in young children. Fifteen articles were identified that reported on ER in children with ASD and had participants that fell within the 12–72 month age range. These articles were systematically reviewed. Children with ASD were found to have a different repertoire of ER strategies and rely more on others to regulate their emotions than their typically developing peers; ASD symptom severity and executive functioning ability were associated with ER abilities; and treatments incorporating both parents and children were found to improve ER abilities in children. Research on ER in young children with ASD is in its infancy with many of the studies reviewed being preliminary in nature. Furthermore, the majority of studies include participants that encompass a broad age range, making it difficult to distinguish the nature and occurrence of ER in toddlers and preschoolers with ASD from ER in older children and adolescence with ASD. Nonetheless, the review provides some insight into the nature of ER in young children with ASD and highlights important directions for future research.